Analyzing Impacts of Transportation Infrastructure and Policies on Traffic Flow in Metro Manila Using Advanced Tools and Techniques. - Regidor, Jose Regin F.
Various transportation infrastructure and policies have been implemented in the Philippines in order to ease traffic congestion and other transportation and traffic problems. Many of these are in Metro Manila, comprising a long list that includes grade separation devices, traffic control facilities, and vehicle restraint measures. These have been generally perceived to have positive impacts and have led to the construction of more infrastructures or the continued implementation of traffic schemes. Nevertheless, there are sectors that have not taken advantage of available impact assessment techniques and tools to systematically and properly evaluate the effects of infrastructure and policies on transportation and traffic. This paper presents the most popular methods and some tools for appraising effectiveness of infrastructure and policies. Several examples are discussed and results are used in formulating recommendations regarding best practices in impact assessment.
Keywords: Impact analysis; Infrastructure; Policies; Traffic flow